Low-dose rivaroxaban plus aspirin in older patients with peripheral artery disease undergoing acute limb revascularization: insights from the VOYAGER PAD trial. (25th August 2021) - Krantz, Mori J; Debus, Sebastian E; Hsia, Judith; Patel, Manesh R; Anand, Sonia S; Nehler, Mark R; Hess, Connie N; Capell, Warren H; Bracken, Taylor; Szarek, Michael; Mátyás, Lajos; Krievins, Dainis K; et al.
Abstract: Aims: In this secondary analysis of the VOYAGER trial, rivaroxaban 2.5 mg twice/day plus aspirin 100 mg/day was assessed in older adults. Advanced age is associated with elevated bleeding risk and unfavourable net benefit for dual antiplatelet therapy in chronic coronary artery disease. The risk–benefit of low-dose rivaroxaban in patients ≥75 years with peripheral artery disease (PAD) after lower extremity revascularization (LER) has not been described. Methods and results: The primary endpoint was a composite of acute limb ischaemia, major amputation, myocardial infarction, ischaemic stroke, or cardiovascular death. The principal safety outcome was thrombolysis in myocardial infarction (TIMI) major bleeding analysed by the pre-specified age cut-off of 75 years. Of 6564 patients randomized, 1330 (20%) were >75 years. Absolute 3-year Kaplan–Meier cumulative incidence rates for primary efficacy (23.4% vs. 19.0%) and safety (3.5% vs. 1.5%) endpoints were higher in elderly vs. non-elderly patients. Efficacy of rivaroxaban ( P -interaction 0.83) and safety ( P -interaction 0.38) was consistent irrespective of age. The combination of intracranial and fatal bleeding was not increased in patients >75 years (2 rivaroxaban vs. 8 placebo). Overall, benefits (absolute risk reduction 3.8%, number needed to treat 26 for the primary endpoint) exceeded risks (absolute risk increase 0.81%, number needed to harm 123 for TIMI major bleeding). Conclusion: Patients ≥75 years with PAD are at both heightened ischaemic and bleeding risk after LER. No excess harm with respect to major, intracranial or fatal bleeding was seen in older patients yet numerically greater absolute benefits were observed. This suggests that low-dose rivaroxaban combined with aspirin should be considered in PAD after LER regardless of age. Graphical Abstract: